Nur Najihah Solutions / Muhammad Syahir Ahmad - Ahmad, Muhammad Syahir (2020)
Fundamental of Entrepreneurship (ENT300) required me to carry out a case study. In the case study, I need to collect all information about the company that I chose to complete the case study. In order to fulfil the requirements, I decided to contact Nur Najihah Solutions Founder to do an interview session which is Ms.Nurmasturina Najihah Binti Hassin. The interview cannot be held in physical way due to Movement Control Order and COVID-19 increasing cases, so I decided to make an interview session through WhatsApp application and through phone calls. The interview has helped me to collect the information such as their company background, entrepreneur profile, business profile, products that they made and many more.